The Ethics of Environmental Concern - Attfield, Robin (University of Georgia Press, 1991)
First published in 1983, The Ethics of Environmental Concern has become a classic in the relatively new field of environmental ethics. Examining traditional attitudes toward nature, and the degree to which these attitudes enable us to cope with modern ecological problems, Robin Attfield looks particularly at the Judeo-Christian heritage of belief in humankind's dominion, the tradition of stewardship, and the more recent belief in progress to determine the extent to which these attitudes underlie ecological problems and how far they embody resources adequate for combating such problems. He then examines concerns of applied ethics and considers our obligations to future generations, the value of life, and the moral standing and significance of nonhumans. Simultaneously, he offers and defends a theory of moral principles appropriate for dealing with such concerns as pollution, scarce natural resources, population growth, and the conservation and preservation of the environment.The second edition includes a new preface and introduction, as well as a bibliographic essay and an updated list of references incorporating relevant scholarship since the publication of the first edition.